Investigation into the role of silica in lithium polysulfide adsorption for lithium sulfur battery. (September 2015) - Kim, Miso; Kang, Sung-Hwan; Manuel, James; Zhao, Xiaohui; Cho, Kwon Koo; Ahn, Jou Hyeon
Graphical abstract: Highlights: Amine functionalized silica nanoparticles (AFSN) were prepared. Polysulfide adsorption studies were carried out with silica nanoparticles and AFSN. Sulfur cathodes were prepared with SN and AFSN for Li–S batteries. AFSN showed excellent polysulfide adsorption. Abstract: A new type of sulfur electrodes with the ability for polysulfide adsorption was prepared by incorporating silica nanoparticles (SN) or amine functionalized silica nanoparticles (AFSN). AFSN was synthesized by a simple and cost-effective method. The functionalization and surface morphology of silica were confirmed with Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM), respectively. Polysulfide adsorption studies were carried out using UV–vis spectrometer, which confirmed the excellent adsorption of polysulfides by AFSN. Interaction of polysulfides with SN or AFSN was studied using FTIR and FT-Raman spectroscopy. The effective polysulfide adsorption by SN and AFSN leads to good and stable cycle performance of lithium sulfur cells. The results show that the incorporation of SN or AFSN with sulfur is a promising method to prepare cathode material for lithium sulfur batteries.